Analisis Kesalahan Ejaan Dalam Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 1 Cilebar - Mia Munaroh; Sinta Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to describe the spelling errors contained in the descriptive essays of Cilebar 1 Public Middle School students. The spelling errors include: a) capitalization errors, b) errors in the use of -di and -ke prepositions c), -di and -ke affix errors, d) punctuation errors. The subject of this research is the writing of class VII students of Cilebar Public Middle School. The objects of this study were students who made descriptive texts using data collection techniques in the form of documentation and observation. The results of this study are as follows. First, capital letter errors were found in 64 cases because students still could not determine which words had the first letter capitalized, besides that the most dominant capital letter errors were found. Second, there were 3 cases of errors in writing prepositions. Third, errors in writing affixes were found in 5 cases because in this case there were still students who could not distinguish between the prepositions -di and -ke and the affixes -di and -ke. Fourth, there were 17 cases of writing punctuation errors, while comma errors were found in 5 cases. This is because students have not been able to determine the position of the comma and full stop in a sentence